Is Pulmonary non-Tuberculous Mycobacterial Disease Linked with a High Burden of Latent Cytomegalovirus? - Amran, F.; Kim, K.; Lim, A.; Thomson, R.; Lee, S.; Waterer, G.; Price, Patricia (2016)
© 2016 Springer Science+Business Media New York. Cytomegalovirus (CMV) establishes lifelong infections with episodes of active replication. We hypothesized that recurrent CMV replication in older individuals may suppress protective immune responses to non-tuberculous mycobacteria (NTM) and so potentiate pulmonary disease. Accordingly, levels of antibodies to three CMV antigen preparations were higher in NTM patients than in age-matched controls. This did not reflect broad-spectrum B cell activation as total immunoglobulin levels were not equivalently increased.